2004
DOI: 10.1128/aem.70.5.2709-2716.2004
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Spatial Distribution of 2,4-Dichlorophenoxyacetic Acid Degrader Microhabitats during Growth in Soil Columns

Abstract: Bacterial processes in soil, including biodegradation, require contact between bacteria and substrates. Knowledge of the three-dimensional spatial distribution of bacteria at the microscale is necessary to understand and predict such processes. Using a soil microsampling strategy combined with a mathematical spatial analysis, we studied the spatial distribution of 2,4-dichlorophenoxyacetic acid (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
60
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 33 publications
3
60
0
Order By: Relevance
“…Moreover, the bacterial distribution at the microscale may facilitate spreading of degradative genes located in plasmids or transposons (McGowan et al, 1998;DiGiovanni et al, 1996). Pallud et al (2004) found that for low abundances of 2,4 D degraders, there was strong spatial isolation within the degraders populations, with less than 2 cells per colonized patch. 2,4-D amendment caused an increase in degrader abundance and concurrent spreading of degraders, reducing the distance between colonized patches, although the number of cells per patch remained low (< 28).…”
Section: Spatial Distribution Of Microbial Populationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the bacterial distribution at the microscale may facilitate spreading of degradative genes located in plasmids or transposons (McGowan et al, 1998;DiGiovanni et al, 1996). Pallud et al (2004) found that for low abundances of 2,4 D degraders, there was strong spatial isolation within the degraders populations, with less than 2 cells per colonized patch. 2,4-D amendment caused an increase in degrader abundance and concurrent spreading of degraders, reducing the distance between colonized patches, although the number of cells per patch remained low (< 28).…”
Section: Spatial Distribution Of Microbial Populationsmentioning
confidence: 99%
“…2,4-D amendment caused an increase in degrader abundance and concurrent spreading of degraders, reducing the distance between colonized patches, although the number of cells per patch remained low (< 28). They argued that the spatial spreading of bacteria was an ecological strategy that increased the probability of encountering the substrate (2,4-D), and proposed that this was achieved either through active cell movement (chemotaxis) or degradative plasmids transfer to indigenous microbial populations (Pallud et al, 2004). The zone of soil directly influenced by the presence of plant roots, known as rhizosphere, is of particular importance.…”
Section: Spatial Distribution Of Microbial Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our experimental set-ups, the soil microbial status were strongly constrained by the organization of the solid substrate that differed significantly from homogeneous soil/solution suspensions to well structured porous media. These two types of organization may have a great influence on the microbial development strategy leading to various microbial, solid and liquid interfaces [12]. Thus, combining both static and dynamic experiments allowed to check the accuracy of biotic and abiotic sorption parameters to characterize radionuclide mobility.…”
Section: Column Experimentsmentioning
confidence: 99%
“…Using microscopic techniques, Nunan and coworkers have described the in situ distribution of soil bacteria at multiple scales (31) and with respect to soil porosity (32). The three-dimensional microscale distributions of specific autochthonous functional communities have been characterized as well, by an approach based on soil microsampling for with nitrifiers (14) and 2,4-dichlorophenoxyacetic acid (2,4-D) degraders (34).…”
mentioning
confidence: 99%